Analysis of Liquidity, Solvability, and Profitability Levels as a Tool for Assessing the Financial Performance of PT. Megapower Makmur TBK - Ainur Rahmah Julista; Apriliana Apriliana; Dian Pratika Sari; Herlin Febrian; Jini Liana; Windi Windi; Herayati Herayati (Nomico, 2026)
This study aims to evaluate the financial performance of PT Megapower Makmur Tbk. (MPOW) in the 2022–2024 period using Liquidity ratio analysis (Current Ratio and Quick Ratio), Solvency (Debt to Asset Ratio and Debt to Equity Ratio), and Profitability (Return on Assets and Return on Equity). The method applied is descriptive quantitative, utilizing secondary data from the IDX Financial Report. The results show that the company's liquidity level is in poor condition, because current assets are insufficient to meet its short-term liabilities (CR and QR are far below the industry standard of 200% and 100%). In terms of solvency, the company shows a continuous improvement trend with a decrease in DAR and DER values, indicating that dependence on debt is decreasing. Meanwhile, profitability performance continues to show poor results, with net income remaining negative from 2022 to 2024. Therefore, management is advised to restructure short-term debt and evaluate operational cost efficiency to restore profitability.